Common fixed point theorems for a weak distance in complete metric spaces - Jeong Sheok Ume; Sucheol Yi (International Journal of Mathematics and Mathematical Sciences)
Using the concept of a w-distance, we obtain common fixed point theorems on complete metric spaces. Our results generalize the corresponding theorems of Jungck, Fisher, Dien, and Liu.